A Mouse Model of Metabolic Syndrome: Insulin Resistance, Fatty Liver and Non-Alcoholic Fatty Pancreas Disease (NAFPD) in C57BL/6 Mice Fed a High Fat Diet - Julio Cesar Fraulob; Rebeca Ogg-Diamantino; Caroline Fernandes‐Santos; Márcia Barbosa Águila; Carlos Alberto Mandarim‐de‐Lacerda (2010)
Diet-induced obesity in C57BL/6 mice triggers common features of human metabolic syndrome (MetS). The purpose is to assess the suitability of a diet-induced obesity model for investigating non-alcoholic fatty pancreatic disease (NAFPD), fatty liver and insulin resistance. Adult C57BL/6 mice were fed either high-fat chow (HFC, 60% fat) or standard chow (SC, 10% fat) during a 16-week period. We evaluated in both groups: hepatopancreatic injuries, pancreatic islets size, alpha and beta-cell immunodensities, intraperitoneal insulin tolerance test (IPITT) and oral glucose tolerance test (OGTT). The HFC mice displayed greater mass gain (p<0.0001) and total visceral fat pads (p<0.001). OGTT showed impairment of glucose clearance in HFC mice (p<0.0001). IPITT revealed insulin resistance in HFC mice (p<0.0001). The HFC mice showed larger pancreatic islet size and significantly greater alpha and beta-cell immunodensities than SC mice. Pancreas and liver from HFC were heavier and contained higher fat concentration. In conclusion, C57BL/6 mice fed a high-fat diet develop features of NAFPD. Insulin resistance and ectopic accumulation of hepatic fat are well known to occur in MetS. Additionally, the importance of fat accumulation in the pancreas has been recently highlighted. Therefore, this model could help to elucidate target organ alterations associated with metabolic syndrome.